Pelatihan Pemanfaatan Media Sosial Untuk Pemasaran Produk UMKM Di Kelurahan Pancoran Mas, Depok - Shanti Darmastuti; Mansur Juned; Danis Tri Saputra; Faradilla Indah Siti Aysha; Yulan Adi Nugroho; Nofa Ksatria (AMMA : Jurnal Pengabdian Masyarakat, 2025)
Using social media in product marketing is an innovative way to expand the market. Through social media, business actors, including Micro, Small, and Medium Enterprises (MSMEs), have the convenience of marketing products online. Understanding the correct utilization of social media is essential for MSMEs. Therefore, community service activities carried out in Pancoran Mas Village, Depok, aim to provide training on the use of social media for marketing MSME products. This training was attended by representatives of MSME players in Pancoran Mas Village who are engaged in various fields, including fashion, food, and crafts. The training activities also invited resource persons who have successfully run their businesses in the fashion sector. The training activities were carried out in several stages starting from coordination, filling in the pre-test, training on the use of social media, and filling in the post-test. Through training and sharing sessions, participants gained insights to strengthen their capacity to market their products through social media. The participants  well-received training on the utilization of social media.